Vaccine cold chain in general practices: A prospective study in 75 refrigerators (Keep Cool study) - Thielmann, Anika (PLoS One, 2019)
INTRODUCTION: Protecting vaccines from freeze damage is considered one of the most poorly addressed problems in vaccine management. Freezing may impair the potency especially of adsorbed vaccines. The Keep Cool study aims at ensuring optimal vaccine storage conditions in general practices. This publication analyses the baseline data using standardised temperature recordings. METHODS: This prospective study in German general practices analysed 7-day temperature recordings of refrigerators used for vaccine storage. Temperatures were recorded continuously using a standardised data logger with an accuracy of ±0.4 °C. The prevalence rates of refrigerators within the target range (2 to 8 °C) and of those reaching critically low temperatures (≤0 °C) were calculated. In addition, the cumulative time and the duration of single episodes beyond the target range were computed. To assess for structural deficits, the prevalence of refrigerators with a cycling of >5 °C was determined. Generalised linear mixed models were applied to analyse correlating factors between the dependent variables ‘within temperature range’ and ‘reaching critically low temperatures’ with practice characteristics. RESULTS: The study included 64 of 168 practices (38.1% response rate) with 75 refrigerators. The prevalence of refrigerators with temperatures within the target range was 32.0% (n = 24), and 14.7% (n = 11) reached critically low temperatures <0 °C. 44.0% of refrigerators (n = 33) showed temperatures >8 °C and 28.0% (n = 21) <2 °C. Of the 168 hours recorded per refrigerator, the average cumulative time >8 °C was 49 hours, <2 °C 75 hours and ≤0 °C 74 hours. The longest consecutive period of critically low temperatures was 168 hours (mean: 39±53). The prevalence of refrigerators with a cycling range of >5 °C was 29.3%. CONCLUSION: Given the importance of immunisation, the results of our study call for action, as two-thirds of the refrigerators exhibited cold chain breaches and 15% reached critically low temperatures threatening vaccine potency.